2010
DOI: 10.1021/ef100645b
|View full text |Cite
|
Sign up to set email alerts
|

On the Nanofiltration of Asphaltene Solutions, Crude Oils, and Emulsions

Abstract: It has long been established that crude oils contain a colloidal suspension of asphaltenes where the mass fraction can range from 0 to 15%. The size of the colloidal particles is less well understood. Crude oil properties depend critically on the asphaltene content, yet measurement of these properties can be hindered by emulsified water and inorganic particulates in heavier crude oils. Here we explore the ability to isolate pure and unaltered crude oil samples using Gore-Tex membranes with nominal pore sizes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 49 publications
0
25
0
1
Order By: Relevance
“…They revealed that the asphaltene aggregates are smaller than the normal pore size of the membrane, i.e. 30 nm . Tabatabaei‐nejad et al .…”
Section: The Size and Structure Of Asphaltene Aggregatesmentioning
confidence: 99%
“…They revealed that the asphaltene aggregates are smaller than the normal pore size of the membrane, i.e. 30 nm . Tabatabaei‐nejad et al .…”
Section: The Size and Structure Of Asphaltene Aggregatesmentioning
confidence: 99%
“…The clusters form only at much higher concentration (see Figure 8) because the attractive forces of one nanoaggregate to another are much weaker. Nanofiltration studies indicate that the size of clusters is smaller than 30 nm (Ching et al, 2010). Very recent SAXS and SANS studies revealed that asphaltene clusters consist of 12 nanoaggregates and, due to their fractal nature, they are very sensitive to temperature variations and solvent type (Eyssautier et al, 2011b).…”
Section: Structure and Role Of Resinsmentioning
confidence: 99%
“…The concentration at which this dramatic change in the kinetics of flocculation takes place is called the critical clustering concentration (CCC ≈ 2–5 g/L , ). Although ultrafiltration studies confirm that the clusters are in nanoscale (smaller than 30 nm), the clusters can form fractal aggregates with dimensions measured from a few to several hundred micrometers . It is evident that asphaltenes are suspended as a true molecular solution, nanoaggregates, and clusters of nanoaggregates in light (i.e., asphaltene content ≪1 wt %), intermediate, and heavy oils (i.e., asphaltene content around 10 wt %), respectively. , Such observations have provided valuable insight into the aggregation and solubility behavior of asphaltenes.…”
Section: Introductionmentioning
confidence: 99%